(untitled) (Journal of Ideas in Health, 2023)
Background: Increasing population, limited resources, and climate change require adopting more sustainable diets. This study aims to evaluate health professionals’ knowledge levels and practices on sustainable nutrition. Methods: A cross-sectional study was conducted between January 2022 and May 2022 at Dr. Abdurrahman Yurtaslan Oncology Training and Research Hospital in Ankara. The research was performed by using the "Stretched Sampling Method". A semi-structured and self-reported online survey was recruited to collect data from healthcare professionals. Data from 298 participants were subjected to descriptive and univariate analyses to evaluate differences in knowledge mean scores and SCOFI scores. The data analysis results with the SPSS 26.0 program were accepted as a 95% confidence interval, with significance p≤0.05. Result: A total of 298 people participated in the study. The mean age of respondents was 36 years (13±10.8). More than two-thirds (79.2%) were females, more than half (52%) were nurses, 20.5% were doctors, 60.4% had a bachelor’s degree, % and 12.8 had a master’s degree. Sustainable nutrition knowledge and SCOFI mean scores were 10.71±5.3 (0-24) and 54.09±13.2, respectively. 37.9% of the participants stated that they had heard of the concept of sustainable nutrition before. The sustainable nutrition knowledge of females was lower, and the SCOFI score was higher (P>0.05). The SCOFI score of the 18-25 age group was lower than the other age groups (P<0.05). Sustainable nutrition knowledge means scores increased as the education level increased (P<0.05). Dieticians had the highest sustainable nutrition knowledge and SCOFI score (P<0.05). The SCOFI score of those working in the surgery room and intensive care unit was lower than the other units (P<0.05). Conclusion: Training for healthcare professionals might increase sustainable nutrition knowledge and awareness.